COMPARATIVE ANALYSIS OF DESIGN SETTLEMENT FOUNDATIONS METHODS ACCORDING TO DATA OF CONE PENETRATION TEST ON NATIONAL AND EUROPEAN STANDARDS - Kremniov, A. P.; Lobacheva, N. G. (Academic journal Industrial Machine Building Civil Engineering, 2017)
It is given a comparative analysis of the methods of computation of foundations settlement according to Cone Penetration Test with the current normative documents of the Republic of Belarus and the Eurocode 7 «Geotechnical design» (part 1, 2). Three methods of computation of foundation settlement for the sediment limit state SLS are considered in accordance to European standards and two methods of computation of foundation settlement are considered in accordance to National standards. The similarities and the differences in construction of the conditional pile foundation are identified according to National and European standards. The similarities and the differences in the methods of foundation settlement computation in accordance to European and National standards are revealed and summarized. The difference of the calculated values of foundation settlement is defined in percentage.